Arsip Digital dan Memori Kolektif Sebagai Ruang Publik dalam Pelestarian Sejarah Tionghoa di Indonesia - Alexander Raymon; Nina Witasari (Policy, Law and Political Research Center, 2026)
This study examines digital archives and collective memory in preserving the history of the Chinese community in Indonesia. From the colonial period through the New Order era, Chinese history experienced marginalization due to discriminatory policies and limited access to official state archives, hence being excluded from national historiography. In the Post-Reformation period, digital technology has opened new opportunities for the state, public institutions, and civil society to reconstruct, manage, and disseminate historical archives in a more inclusive manner. This research uses a descriptive qualitative approach with thematic analysis of digital archives, museums, community initiatives, manuscript digitization projects, and online platforms that play a role in preserving collective memory. The findings indicate that digital archives function as a public sphere that enables community participation, intergenerational dialogue, and reconciliation. The implications of this study highlight the importance of open digital archiving policies within public administration to ensure pluralistic historiography and public participation. This research recommends strengthening collaboration between government institutions, academic centers, and community-based organizations to sustain collective memory in the digital era.